Hair penalties: the negative influence of Afrocentric hair on ratings of Black women’s dominance and professionalism - Opie, Tina R.; Phillips, Katherine W. (Frontiers in Psychology, 2015)
Purpose: Women are penalized if they do not behave in a stereotype-congruent manner (Eagly & Carli, 2007; Heilman, 1983; 2001). For example, because women are not expected to be agentic they incur an “agency penalty” for expressing anger, dominance or assertiveness (Brescoll & Uhlmann, 2008; Eagly & Karau, 2002; Livingston, Rosette, & Washington, 2012; Rudman, 1998; Rudman & Fairchild, 2004; Rudman & Glick, 1999, 2001). Yet, all women are not equally penalized (Livingston, Rosette, & Washington, 2012). We make a novel contribution by examining how both White and Black evaluators respond to Black women’s dominance, in this case, whether Black women choose to wear Afrocentric or Eurocentric hairstyles. Design/methodology/approach: We conducted three experimental studies to examine the influence of target hairstyle and participant race on ratings of the target’s professionalism (Studies 1, 2 and 3) and dominance (Study 2). Study 1 was an online experimental study with 200 participants (112 females, 87 males, 1 missing gender; 160 Whites, 19 Blacks, 11 Latinos, 7 Asian Americans and 3 who identify as “other”; Mage= 35.5, SD = 11.4). Study 2 was an online experimental study with 510 participants (276 women, 234 males; 256 Blacks, 254 Whites; Mage = 41.25 years, SD = 12.21). Study 3 was an online experimental study with 291 participants (141 Blacks, 150 Whites, Mage= 47.5 years, SD = 11.66). Findings: Black, as compared to White, evaluators gave higher agency penalties to Black employment candidates when they donned Afrocentric versus Eurocentric hair, rating them as more dominant and less professional. Implications: The present research illustrates the significance of considering both target and evaluator race when examining the influence of agency, and specifically dominance, on ratings of professionalism.